Result Analysis Physical Fitness Test Candidate Students Police Academy At Pt. Ock Klub Atletik Year 2023 - Supriyatnak, Kokom (Lembaga Penelitian dan Pendidikan Mandala, 2023)
PT. OCK Klub Atletik is a guidance institution physical programs, academic programs and psychology programs for interested candidate students and prepare for member entry TNI, Police and other official schools. Physical programs are physical exercise programs to improve the results of physical abilities and efforts to fulfill standardization on physical testing. The purpose of this study is to find out the results physical abilities and results standardization of physical fitness test police in students PT. OCK Klub Atletik year 2023. In this study using a method design survey forms of quantitative descriptive research by using instruments research in the form of tests. Sampling is carried out by technique total sampling so that the research subjects amounted to 152 persons. Physical test measurements according to standard instruments police. The results of the study were physical abilities with a very good category of 4 persons (3%), goodness 66 persons (43%), enough 60 persons (39%), K1 12 persons (8%) and K2 10 persons (7%) then results standardization pass limit qualified 132 persons (87%) and unqualified 20 persons (13%).